2020
DOI: 10.1021/acs.jproteome.0c00646
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Very-Low-Calorie Ketogenic Diet on Psoriasis Patients: A Nuclear Magnetic Resonance-Based Metabolomic Study

Abstract: Psoriasis is an inflammatory disease of the epidermis based on an immunological mechanism involving Langerhans cells and T lymphocytes that produce pro-inflammatory cytokines. Genetic factors, environmental factors, and improper nutrition are considered triggers of the disease. Numerous studies have reported that in a high number of patients, psoriasis is associated with obesity. Excess adipose tissue, typical of obesity, causes a systemic inflammatory status coming from the inflammatory active adipose tissue;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 70 publications
(130 reference statements)
0
64
0
4
Order By: Relevance
“…For instance, the LCHF diet significantly reduced ceramides in pancreatic cancer patients postpancreatectomy which are metabolic biomarkers of CMDs as well 250 . Another example of this regulatory effect had been seen with psoriasis disease regression in psoriasis patients following the LCHF diet as a nutritional anti‐inflammatory therapy 251 . The LCHF diet significantly reduced lactic acid, isoleucine, leucine, and alanine in psoriasis patients treated with this dietary approach.…”
Section: Cmds Therapeutic‐metabolomic: Current State and Future Perspmentioning
confidence: 98%
See 1 more Smart Citation
“…For instance, the LCHF diet significantly reduced ceramides in pancreatic cancer patients postpancreatectomy which are metabolic biomarkers of CMDs as well 250 . Another example of this regulatory effect had been seen with psoriasis disease regression in psoriasis patients following the LCHF diet as a nutritional anti‐inflammatory therapy 251 . The LCHF diet significantly reduced lactic acid, isoleucine, leucine, and alanine in psoriasis patients treated with this dietary approach.…”
Section: Cmds Therapeutic‐metabolomic: Current State and Future Perspmentioning
confidence: 98%
“…Unlike the Mediterranean diet, the metabolomic data on the role of LCHF diet in CMDs treatment are limited. The LCHF effect on the metabolome has been investigated in cancer and epilepsy as well as in inflammatory diseases such as psoriasis 250–252 ; however, to the best of this author's knowledge, the LCHF‐metabolomic study has not yet been applied to CMDs. Some of the LCHF metabolomic studies investigating non‐CMDs diseases indicated a regulatory effect of the diet on some metabolites implicated in the shared metabotype of CMDs.…”
Section: Cmds Therapeutic‐metabolomic: Current State and Future Perspmentioning
confidence: 99%
“…Similarly, another recent study investigated the effect of low-calorie ketogenic diet in 30 patients with psoriasis by evaluating clinical symptoms, biochemical markers, metabolomic profile and inflammatory markers (IL-2, IL-4, IL-1β, TNF-α, IFN-γ). Four-weeks of VLCKD resulted in 10% weight loss, 50% reduction in PASI score, improvement of biochemical markers related to psoriasis (folic acid, vitamin B12, cortisol, bilirubin, calcium, LDL, cholesterol) and decreased IL-1β and IL-2 levels [ 189 ]. Based on this data, ketogenic diet is a promising prospect in psoriasis management, but large studies are needed for safe conclusions.…”
Section: Diet and Psoriasis: Obesity Dietary Regimens And Promisimentioning
confidence: 99%
“…Generally, psoriatic disease-related metabolomics studies aim to identify metabolic markers that can be used for Ps and/or PsA diagnosis. While a few studies have examined the metabolite profiles of patients with autoimmune diseases (ADs) [9,10], or immunemediated inflammatory diseases (IMIDs) with no emphasis on Ps or PsA specifically [11], the majority of studies included in this review sought to identify metabolites that were associated with Ps by investigating Ps patients in comparison to healthy volunteers [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Other studies focused on identifying metabolite profiles in Ps patients and correlating them with different measurements of disease activity [13,19,22,28,32,33].…”
Section: The Biological Questionmentioning
confidence: 99%
“…Most studies included in our literature search were non-hypothesis driven and therefore employed an untargeted metabolomics approach [12,[14][15][16][19][20][21][22][23]25,26,[31][32][33]36,41,42]. However, there were several studies that analyzed specific metabolites using a targeted metabolomics approach [9,10,13,18,24,27,28,30,39,40].…”
Section: Experimental Designmentioning
confidence: 99%